Male Sexual Health Related Complications Among Combat Veterans. (23rd August 2022) - Castillo, Otilio; Chen, Irene K.; Amini, Eliad; Yafi, Faysal A.; Barham, David W.
Abstract: Introduction: With improved armor and combat trauma care, more male service members in the 21st century are surviving devastating injuries to their genitourinary (GU) system. The impact of these injuries can have long lasting effect on their sexual function and fertility status. Objectives: To review the current literature on sexual health-related complications and fertility implications among male service members sustaining combat related injuries. Methods: We performed a literature search that included male sexual health complications and combat injuries using PubMed and Google Scholar. We reviewed the impact of traumatic injuries to the pelvis and perineum on sexual function and fertility, and we also discuss sexual dysfunction from posttraumatic stress disorder (PTSD) and traumatic brain injuries (TBI). Results: Injuries sustained during combat are usually polytraumatic, especially in recent conflicts with improvised explosive devices. The majority of GU combat injuries involve the scrotum, testes, and penis resulting in lasting structural dysfunction. PTSD is associated with higher levels of erectile dysfunction, hypoactive sexual desire, and premature ejaculation. Overall, veterans diagnosed with PTSD had a higher risk of developing sexual dysfunction. Veterans with TBI experience sexual health complications, such as decreased libido, difficulties with arousal maintenance, and the ability to achieve orgasm. Combat related injuries can have significant fertility implications on service members as they typically serve in their peak fertility years. Conclusions: Traumatic GU injuries, PTSD, TBI, and associated endocrine dysfunction can all contribute to sexual dysfunction among combat veterans. Given the complex nature of sexual dysfunction in this population, these patients are best managed by a multidisciplinary team.